2020
DOI: 10.3390/molecules26010065
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Solid-State Characterization of Eltrombopag Crystal Phases

Abstract: Eltrombopag, of C25H22N4O4 chemical formula, is a drug used against thrombocytopenia, marketed worldwide under different tradenames in the form of its bis-olamine salt. The free acid (CAS no. 496775-61-2) is an intermediate species used for the final drug isolation and is reported to crystallize in more than 20 distinct crystal forms, including a large number of hydrates and solvates. Their identification, and, ultimately, their quantification in industrial lots require the usage of accurately measured X-ray p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…The results of thermo gravimetric analysis 1) Thermo gravimetric analysis of cinnamon (Abbinante et al, 2020;Aqel et al, 2021;Assali et al, 2020;Bashiri et al, 2021) The thermo gravimetric data of cinnamon are shown in Figure 2, Figure 3 and Table 2. It can be seen from 3) Thermogravimetric analysis of clove…”
Section: Thermo Gravimetric Analysis Of 5 Kinds Of Condimentsmentioning
confidence: 99%
“…The results of thermo gravimetric analysis 1) Thermo gravimetric analysis of cinnamon (Abbinante et al, 2020;Aqel et al, 2021;Assali et al, 2020;Bashiri et al, 2021) The thermo gravimetric data of cinnamon are shown in Figure 2, Figure 3 and Table 2. It can be seen from 3) Thermogravimetric analysis of clove…”
Section: Thermo Gravimetric Analysis Of 5 Kinds Of Condimentsmentioning
confidence: 99%
“…Eltrombopag (EP), a non-peptide small molecule agonist of the human thrombopoietin receptor (TpoR), was discovered by screening small molecular libraries to bind TpoR and stimulate its downstream signaling, and further rationally designed to improve yielding and purity ( Bussel et al, 2019 ). The bisolamine salt EP Olamine [EP(O)] is the most common formulation, which was found to be easily produced, orally ingestible and environmentally stable ( Abbinante et al, 2020 ). EP is mainly used in the oral treatment of idiopathic thrombocytopenic purpura (ITP) ( Erickson-Miller et al, 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…Conventional experimental methods employed to assess, at constant pressure, the relative thermal stability of polymorphs are thermoanalytical (DSC/TGA) or variable-temperature X-ray powder diffraction (VTXRD) analyses. Coupling these two techniques with structural powder diffraction analysis, which can provide atomic-scale models of polymorphs that cannot be isolated as single crystals of suitable size and quality, is now possible, and has largely benefited from the pioneering work of a few academic research groups [ 13 ], including ours [ 14 ].…”
Section: Introductionmentioning
confidence: 99%